Efficient photocatalytic degradation of methyl violet using two new 3D MOFs directed by different carboxylate spacers - Wang, Jun; Rao, Congying; Lu, Lu; Zhang, Shile; Muddassir, Mohd; Liu, Jianqiang (CrystEngComm, 2021)
Two highly stable metal-organic frameworks (MOFs) assembled by a flexible 1,4-bis(2-methylimidazol-1-yl)butane (bib), and two different aromatic carboxylate coligands, namely, [Zn(BDC-OH 2 )(bib)] ( 1 ) and [Cd 3 (BTC) 2 (bib)(DMF) 3 ] ( 2 ) (H 2 BDC-OH 2 = 2,5-dihydroxyterephthalic acid, H 3 BTC = 1,3,5-benzenetribenzoic acid), were designed and synthesized. 1 showed a 4-fold interpenetration of 4-connected dia-type topological net. In 2 , the 3D topological structure can be viewed as a (3,4,5)-connected network, and its Schläli point is {4·6 2 } 2 {4 2 ·6·8 3 } {4 6 ·8 9 }. Different auxiliary carboxylate ligands were examined with respect to the building of various structures. 1 and 2 have outstanding photocatalytic behaviors for the disintegration of methyl violet (MV) under UV irradiation. Both the MOFs proved to be good candidates for the photocatalytic degradation of methyl violet. The mechanism of these photocatalytic degradations is discussed.